The Effect of Reynolds Number on 90° PVC Elbow Minor Loss Coefficient - Suhaimi, Muhammad Syakir; Idris, Ahmad Fu'ad (Research Progress in Mechanical and Manufacturing Engineering, 2023)
The objective of this project is to find the effect of the Reynolds number on the 90-degree PVC elbow minor loss coefficient value. Based on (Robert H. Perry & Don W. Green, 2008), the minor loss coefficient for a 90-degree elbow has a constant value of 0.75. An apparatus was built to find the relationship between these two parameters. Based on the experiment result, the value of the minor loss coefficient is inversely proportional to the Reynolds number. As the Reynold number increases, the minor loss coefficient’s value decrease. At low Reynolds number, the rate of minor loss coefficient value decreasing is huge, while at high Reynolds number, the rate is small. The correlation and regression methods were applied to find the best relationship between the Reynolds number and the minor loss coefficient value. The result shows that the cubic equation was the best relationship between the Reynolds number and the minor loss coefficient value. The equation is kL=-9x10-14Re3+9x10-9Re2-0.0003Re+4.2506 with the value of R and R2 are 0.9775, 0.9557 respectively.